2011
DOI: 10.1038/mi.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

Sustained TL1A expression modulates effector and regulatory T-cell responses and drives intestinal goblet cell hyperplasia

Abstract: The tumor necrosis factor (TNF) superfamily protein TNF-like 1A (TL1A) is the ligand for death receptor 3 (DR3). TL1A is induced on activated dendritic cells (DCs) and its expression has been linked to human inflammatory bowel disease. To address how TL1A might influence intestinal inflammation, we generated transgenic mice that constitutively express TL1A on DCs. TL1A transgenic mice developed striking goblet cell hyperplasia in the ileum that was associated with elevated interleukin (IL)-13 levels in the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
101
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 48 publications
13
101
0
5
Order By: Relevance
“…We suspect that these differences arise from distinct requirements for the upregulation of CD30L and OX40L when compared to TL1A. This notion is supported by previous findings showing that TL1A, but not OX40L, is upregulated on dendritic cells by TLR4 stimulation and conversely upregulation of OX40L, but not TL1A, is induced by anti-CD40 stimulation [5,15,30,31]. Interestingly, in phylogenetic trees of TNF superfamily members OX40L and CD30L are found in one cluster These are not the final page numbers and TL1A and TNF-a are present in a second cluster suggesting that the two groups could have evolved in response to different selective pressures [32].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We suspect that these differences arise from distinct requirements for the upregulation of CD30L and OX40L when compared to TL1A. This notion is supported by previous findings showing that TL1A, but not OX40L, is upregulated on dendritic cells by TLR4 stimulation and conversely upregulation of OX40L, but not TL1A, is induced by anti-CD40 stimulation [5,15,30,31]. Interestingly, in phylogenetic trees of TNF superfamily members OX40L and CD30L are found in one cluster These are not the final page numbers and TL1A and TNF-a are present in a second cluster suggesting that the two groups could have evolved in response to different selective pressures [32].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, addition of TL1A enhanced the proliferation of in vitro generated Th17 cells upon re-stimulation, but had no effect on the proliferation of Th1 cells [13]. Consistent with these findings transgenic mice that constitutively express TL1A have increased levels of IL-13 and IL-17 but not IFN-g under steady-state conditions [15,16]. However, other studies have shown that addition of TL1A or agonist anti-DR3 mAb enhances the production of both IL-4 and IFN-g during in vitro activation of naïve CD4 1 T cells [5,14].…”
Section: Introductionsupporting
confidence: 66%
“…Therefore, a comparison with the functional effects of the natural ligand, TL1A, is necessary. Consistent with the effects elicited by 4C12, transgenic overexpression of TL1A resulted in increased numbers of Tregs, but TL1A-transgenic overexpression also led to modulation of CD4 + Tconv responses, intestinal goblet cell hyperplasia, and intestinal inflammation (14,(41)(42)(43), indicating important regulatory functions of TL1A, especially in the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 53%
“…Stimulation of TNFRSF25 inhibits Treg suppressive function (14), similar to what has been described for GITR, OX40, and 4-1BB (1,(15)(16)(17). Moreover, OX40 triggering also inhibits the de novo biogenesis of Foxp3 + -induced Tregs (iTregs) that differentiate from CD4 + Foxp3 2 conventional T cells (Tconvs) in the presence of TGF-b (18)(19)(20).…”
Section: S Everal Members Of the Tnf Superfamily Expressed By T Cellsmentioning
confidence: 77%
“…TL1A costimulates T-cell production of effector cytokines in vitro [4,[6][7][8] and enhances the accumulation of CD4 1 effector T cells within the inflamed tissues in autoimmune and inflammatory disease models [6]. TL1A also promotes Treg proliferation and attenuates Treg-mediated suppression of non-regulatory CD4 1 T cells [9]. In addition, TL1A has been shown to costimulate invariant NKT cells [10] and may have a role in enhancing NK cell-mediated tumor cell killing [11].…”
Section: Introductionmentioning
confidence: 99%